Bailey and Love's Essential Clinical Anatomy - Lumley, J. S. P. (John Stuart Penton); Craven, J. L. (John Leonard); Abrahams, Peter H.; Tunstall, Richard (Associate professor of anatomy) (Milton : Chapman and Hall/CRC, 2018)
This essential companion to Bailey & Love's Short Practice of Surgery covers the clinical conditions most commonly encountered by medical students, junior clinicians, and surgeons in training. This is clinical anatomy at its best! Structured by body region, each chapter includes plentiful clinical photographs and images supplementing the high-quality anatomical diagrams, using the best modality to demonstrate anatomical relevance. Highlighted descriptions of clinical relevance emphasise the integrated approach so central to current teaching practice, and facilitated by the wealth of both clinical and anatomical experience of the distinguished author team.
12: The shoulder region13: The elbow and forearm; 14: The wrist and hand; PART 5: THE LOWER LIMB; 15: The hip and thigh; 16: The knee, leg and dorsum of the foot; 17: The foot; PART 6: THE HEAD AND NECK; 18: The skull, scalp and face; 19: The orbit, nose and mouth; 20: The temporomandibular joint, pharynx and larynx; 21: The ear, intracranial region and cranial nerves; 22: The neck; 23: Vessels, nerves and lymphatic drainage; 24: Neuroanatomy; 25: The ventricular system, the meninges and blood supply of the cranial cavity; Index.
OCLC-licensed vendor bibliographic record.
Keywords: Human anatomy; MEDICAL -- Surgery -- General